Leisure, ethics, and spirituality. Issue 5 (20th October 2017) - Creighton-Smith, Belinda A.; Cook, Michelle; Edginton, Christopher R.
ABSTRACT: Leisure, ethics, and spirituality are interwoven and contribute to one's leisure choices and behaviours. Spirituality is one component of the quality of one's leisure. Another element of leisure in relationship to spirituality is ethical or moral considerations. The choice of leisure is often governed by one's belief that participation respects one's spiritual convictions and faith traditions. Pieper [2009. Leisure: The Basis of Culture; The Philosophical Act. San Francisco, CA: Ignatius Press, 69] writes, 'the celebration of divine worship, then, is the deepest of the springs by which leisure is fed … though it must be remembered that leisure embraces everything, which without being merely useful, is an essential part of a full human existence'. Spiritual convictions and religious beliefs can provide an ethical framework for decision-making regarding leisure. This paper examines the relationship between spirituality, ethics, and leisure, and how one's spirituality and ethical beliefs may influence leisure choices and experiences.